Prevention of Alveolar Bone Loss of Colocasia Esculenta Varnish. (2022) - Shin, S.J.; Moon, S.H.; Oh, S.H.; Bae, J.M.
Abstract : Purpose/Aim: Periodontitis is the primary cause of tooth loss in adults. Colocasia esculenta extract (CE) was known to have antimicrobial, anti-inflammatory, and anti-osteoclastogenic effects. We fabricated experimental varnish mixed with CE that can be adhered to teeth in the long term. This study aimed to evaluate the prevention effect of the alveolar bone loss of CE varnish using the rat ligature-induced periodontitis model Materials and Methods: The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of CE against Porphyromonas gingivalis were evaluated. Cytotoxicity of CE was determined with a CCK-8 kit for L929 cells. An experimental varnish was fabricated, and 15 wt% CE was mixed with the varnish. Sprague Dawley rats (8-week-old, male) were divided into four groups; Negative control (NC), Positive control (PC), Varnish group(V), and Varnish with CE group(VCE). Periodontitis was induced by ligature of 4/0 silk to the maxillary second molar. In the NC group, the ligation was immediately removed. Then, the varnish was applied around the ligated teeth. After 14 days, the rats were sacrificed, and alveolar bone loss was evaluated using micro-CT. Inflammatory cytokines of the gingiva were analyzed by real-time qPCR. Results: The MIC of CE was 31.3 ?g/mL, and the MBC was 62.5 ?g/mL. CE showed no cytotoxicity at 500 ?g/mL or less. The VCE group showed significantly lower alveolar bone loss than the PC group (p<0.05), but no significant difference from the V group (p>0.05). MMP-9 and IL-6 were significantly lower CEV varnish group than in the V group (p < 0.05). Conclusions: CE was effective in inhibiting P. gingivalis and did not show any cytotoxicity at the antibacterial concentrations. VCE prevented alveolar bone loss in the rat and reduced the expression of inflammatory cytokines. Varnish with CE is regarded to be applied to teeth for the prevention of periodontitis.